2005
DOI: 10.1176/appi.ps.56.7.840
|View full text |Cite
|
Sign up to set email alerts
|

Incarceration Associated With Homelessness, Mental Disorder, and Co-occurring Substance Abuse

Abstract: People who were homeless and who were identified as having mental disorders, although representing only a small proportion of the total population, accounted for a substantial proportion of persons who were incarcerated in the criminal justice system in this study's urban setting. The increased duration of incarceration associated with homelessness and co-occurring severe mental disorders and substance-related disorders suggests that jails are de facto assuming responsibility for a population whose needs span … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
138
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(151 citation statements)
references
References 28 publications
7
138
3
2
Order By: Relevance
“…3 People who are homeless suffer considerably worse health than the general population, 4 contributing to an age-standardized mortality rate up to four times higher among this group. 5,6 Mental disorders are prevalent among homeless people, [7][8][9] with substance dependence the most common diagnosis among homeless populations across the Western world, occurring at rates far exceeding those among the general population. [10][11][12][13][14] A recent meta-analysis indicated that up to 59 % of homeless people are alcohol dependent, and 54 % are dependent on at least one illicit drug.…”
Section: Introductionmentioning
confidence: 99%
“…3 People who are homeless suffer considerably worse health than the general population, 4 contributing to an age-standardized mortality rate up to four times higher among this group. 5,6 Mental disorders are prevalent among homeless people, [7][8][9] with substance dependence the most common diagnosis among homeless populations across the Western world, occurring at rates far exceeding those among the general population. [10][11][12][13][14] A recent meta-analysis indicated that up to 59 % of homeless people are alcohol dependent, and 54 % are dependent on at least one illicit drug.…”
Section: Introductionmentioning
confidence: 99%
“…In one recent study, over three-quarters of inmates with a severe mental disorder also had a cooccurring substance-related disorder; these inmates were more likely to be homeless and to be charged with violent crimes than were other inmates (McNiel, Binder, & Robinson, 2005). A recent review of research that compared offenders with only a mental illness and those with CODs found that those with multiple disorders were more likely to be serving sentences related to their substance use, to be homeless, to violate probation after release, and to recidivate to correctional custody (Hartwell, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…La PD puede afectar el curso clínico de las personas en situación de indigencia, pues se relaciona con un mayor número de recaídas, reingreso a hospitales, severidad de sintomatología, menor adherencia al tratamiento farmacológico, cambios marcados del estado de ánimo e ideación suicida, así como a una mayor exposición a violencia física y sexual, victimización, problemas legales (Jiménez-Castro, Raventós-Vorst, & Escamilla, 2011;Kushel, Evans, Perry, Robertson, & Moss, 2003) y un mayor riesgo de encarcelamiento (McNiel, Binder, & Robinson, 2005). Asimismo, la indigencia está asociada con otras condiciones de salud como la desnutrición, la diabetes, el asma, las cardiopatías y las enfermedades infectocontagiosas (por ejemplo tuberculosis, hepatitis B [VHB], hepatitis C [VHC], VIH), en las que la presencia de la PD dificulta la provisión de atención adecuada (Fazel et al, 2008;Gonzáles & Rosencheck, 2002).…”
Section: Implicaciones De Salud Públicaunclassified
“…Diversos estudios han asociado los trastornos mentales con dificultades de ajuste al ambiente penitenciario, lo cual aumenta el riesgo de presentar abuso y padecer violaciones a los derechos humanos, asimismo dificulta la reintegración social e incrementa las probabilidades de indigencia o reingreso a la cárcel (Mundt et al, 2013;Colmenares-Bermúdez, Romero Mendoza, Rodríguez Ruiz, Durand-Smith, & Saldívar Hernández, 2007;Fazel & Seewald, 2012;McNiel, Binder, & Robinson, 2005). Se ha documentado que es más probable que los reclusos con PD presenten múltiples encarcelamientos o les sea revocada la libertad condicional, comparados con quienes no tienen PD (Baillargeon et al, 2009;Baillargeon et al, 2010;Black et al, 2010;Pickard & Fazel, 2013).…”
Section: Implicaciones De Salud Públicaunclassified